KETERBATASAN SARANA PRASARANA DAN IMPLIKASINYA TERHADAP KREATIVITAS GURU DALAM PEMBELAJARAN INOVATIF DI MI ROUDLOTUL ULUM - Putri, Indri Widia; Muslih, Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a crucial role in developing human resources with a balance of intellectual, spiritual, and moral aspects. However, the limited availability of educational facilities and infrastructure often becomes an obstacle that affects the effectiveness of the pedagogical process. This reality requires educators to optimize their creativity in formulating innovative learning strategies to ensure the maximum achievement of curriculum targets. This study focuses on mapping the condition of physical facilities at MI Roudlotul Ulum, its impact on teaching innovation, and exploring the determinants that influence it. Through a qualitative approach with a case study design, data was collected comprehensively and validated using source triangulation. The research findings indicate that although infrastructure is available, its suitability is still below the ideal standard to support the acceleration of learning quality. These limitations limit the use of learning media and technology, but also encourage teachers to be more creative through the use of simple media and the surrounding environment. Supporting factors include teacher commitment in guiding students, while the main inhibiting factor is the lack of learning facilities and supporting technology.